Studi Kebijakan Dan Implementasi Pp No 33 Tahun 2012 Tentang Pemberian Air Susu Ibu Eksklusif Oleh Tenaga Kesehatan Dan Pemegang Kebijakan Di Kabupaten Buleleng - Ari Pertama Watiningsih; Desak Ketut Sugiartini; Putu Dian Prima Kusuma Dewi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
Optimization of infant growth is still very dependent on nutritional intake, especially breast milk (ASI). Breastfeeding that is not optimal increases the risk of death in infants. The purpose of this study was to determine the perceptions and implementation of health personnel (midwives, nurses, nutritionists) regarding Government Regulation No. 33 of 2012, especially in chapters IV and V. This type of research is a mix method research. The instrument used was a questionnaire. Data analysis using chi square and content analysis. The research was carried out by distributing questionnaires through field surveys to determine policy studies and influencing factors. Implementation was measured by indept interviews. The survey was conducted on midwives, nurses, nutritionists who work in government agencies, namely Puskesmas and policy holders. The results showed that health workers had a good knowledge of 61.54%, a positive attitude of 80.77%, and practiced the implementation of PP No. 33 of 2012 well at 96.15%. There was no knowledge, attitudes and practices related to the implementation of PP No. 33 of 2012. Seacar content that from the results of in-depth interviews that PP No. 33 of 2012 has been carried out optimally and effectively can provide understanding and increase the achievement of exclusive breastfeeding in society.